Factors Related to Behavior in Implementing Patient Safety in Nurses - Supriatin, Eva; Lindayani, Linlin (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Patient safety is an important component in care and measures to improve the quality of service quality. Thestrategy of implementing patient safety has been carried out with various efforts in the hospital environment.The highest number of patient safety data by province in Banten is 125 reports, and Jakarta is 105 reports. Thisstudy aimed to determine factor-factors related to the behavior of the application of patient safetyto the nurseinthe Emergency Room Installation of RSUD dr. Dradjat Prawiranegara in 2018.The study design was crosssectional in which the samples were taken by total sampling method. The study population was nurses in theemergency room of RSUD dr. Dradjat Prawiranegara Serang numbered 37 people. Data collection using aquestionnaire. Univariate research results showed that of 37 respondents 30 respondents (81.1%) had a goodlevel of knowledge, 21 respondents (56.8%) had positive attitudes, 30 respondents (81.1%) had years ofservice≥5 years, and 20 respondents (54.1%) have good behavior. Bivariate analysis results show that there is asignificant relationship between knowledge(P value = 0.002), attitude (P value = 0.003) and work period ≥5years (P value = 0.027) with the application of patient safety behavior to nurses. Researchers expect that thehospital able to refresh the application of patient safety to all nurses on a regular basis every six months.